2020
DOI: 10.3390/v12010089
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Clinical Characteristics of Influenza C Virus

Abstract: Influenza C virus (ICV) is a common yet under-recognized cause of acute respiratory illness. ICV seropositivity has been found to be as high as 90% by 7-10 years of age, suggesting that most people are exposed to ICV at least once during childhood. Due to difficulty detecting ICV by cell culture, epidemiologic studies of ICV likely have underestimated the burden of ICV infection and disease. Recent development of highly sensitive RT-PCR has facilitated epidemiologic studies that provide further insights into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 109 publications
(174 reference statements)
2
40
0
Order By: Relevance
“…In this context, in Japan at least, reemergence of the C/Kanagawa lineage was detected in 1996 and it continued to circulate together with C/São Paulo lineage viruses, which emerged in 2004 and spread widely, throughout the study period and beyond. Our observation of ICV outbreaks occurring 2 years apart in Hong Kong is notable given the evidence of biennial ICV epidemics in Japan ( 7 ), with similar trends having been indicated in studies from other countries, as reviewed in Sederdahl and Williams ( 43 ). The occurrence of biennial epidemics is suggestive of herd immunity temporarily curtailing ICV circulation after each peak of transmission and an inability of the HEF glycoprotein to accommodate frequent antigenic drift substitutions in light of functional constraints.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In this context, in Japan at least, reemergence of the C/Kanagawa lineage was detected in 1996 and it continued to circulate together with C/São Paulo lineage viruses, which emerged in 2004 and spread widely, throughout the study period and beyond. Our observation of ICV outbreaks occurring 2 years apart in Hong Kong is notable given the evidence of biennial ICV epidemics in Japan ( 7 ), with similar trends having been indicated in studies from other countries, as reviewed in Sederdahl and Williams ( 43 ). The occurrence of biennial epidemics is suggestive of herd immunity temporarily curtailing ICV circulation after each peak of transmission and an inability of the HEF glycoprotein to accommodate frequent antigenic drift substitutions in light of functional constraints.…”
Section: Discussionsupporting
confidence: 84%
“…Seropositivity for ICV is as high as 90% in children by 7 to 10 years of age, indicating that it is a major cause of acute respiratory illness that goes undiagnosed due to presentation as mild “cold-like” symptoms in the vast majority of cases ( 42 , 43 ), with only more severe cases seeking medical assistance and even fewer being tested for the virus ( 43 ). This, linked with low isolation rates for ICV, has meant there have been relatively few viruses available for study, and consequently, while numbers of HE gene sequences have been adequate, small numbers of full-genome sequences have been available for analysis ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent developments in RT-PCR for COVID-19 detection have given rise to a greater understanding of the clinical characteristics and molecular epidemiology of COVID-19. 5 Since most of the patients with the earliest onset had been exposed to the south China seafood market in Wuhan, it was widely believed that COVID-19 originated from wild animals sold in the market. Shi et al 6 reported that the natural host of COVID-19 might be bats; the team found that the full genome sequence of the COVID-19 obtained from the confirmed patient was 96% similar to the bat coronavirus, and it was also demonstrated that COVID-19 acts on the receptor angiotensin-converting enzyme 2 through the same cells as severe acute respiratory syndrome coronavirus (SARS-CoV).…”
Section: Introductionmentioning
confidence: 99%
“…Influenza C is a lesser known influenza virus, mostly causing mild upper respiratory infections in children. Influenza C has a worldwide distribution, with a higher seroprevalence in individuals in the third decade of life and progressive decrease in older adults 39 . Despite being known as a cause of mild respiratory infections in young children, it has also been described as a causative agent in severe respiratory infections in adults, particularly among immunocompromised patients 40 .…”
Section: Influenzamentioning
confidence: 99%